Impact of SYNTAX Score on In-hospital Outcome after Primary Percutaneous Coronary Intervention - Islam, Md Shariful; Rahman, Md Afzalur; Chowdhury, Abdul Wadud; Uddin, Sayed Nasir; Kar, Nupur; Karmakar, Kajal Kumar; Firoze, Mohammad Ullah; Rahman, Mohammad Arifur; Khan, Monir Hossen; Ashrafi, Md Nure Alam; et al. (Bangladesh Heart Journal, 2018)
Background: Limited contemporary data exist regarding the impact of SYNTAX score on in-hospital outcomes undergoing primary percutaneous coronary intervention(PCI) in acute STEMI patients. Objectives: To evaluate the significance of the SYNTAX score for predicting in- hospital outcome after primary PCI in patient with acute STEMI. Methods: This cohort study was conducted in the department of cardiology, National Institute of Cardiovascular Diseases, Dhaka, Bangladesh from September, 2015 to September, 2016. 42 patients with acute STEMI who underwent primary PCI were considered for the study. But 2 patients were excluded from the study due to failure of primary PCI. The patients were divided into two groups: Group I (low SYNTAX score d”22) and Group II (high Syntax score > 22). The Syntax score of all patients were calculated from an initial coronary angiogram before primary PCI. In-hospital outcome was observed in between two groups. Results: Among traditional cardiovascular risk factors diabetes was significantly more prevalent in the Group II than Group I ( 82.4% vs 34.8%, p Â 0.003). Angiographic profile revealed maximum (69.6% vs 17.6%) culprit lesion in LAD artery in Group I and maximum culprit lesion (64.7% vs 21.7%) in RCA in Group II, these were the statistically significant between Group I and Group II (P<0.05). The high SYNTAX score group had lower TIMI 3 (76.47% vs 91.3%, p Â 0.03) compared to the low SYNTAX score group. But there were no significant difference in complications as arrhythmia (2.5% vs 0%), cardiogenic shock (2.5% vs 0%), heart failure (5% vs 2.5%) and mortality (5%vs 0%) between high and low SYNTAX score. Multivariate logistic regression analysis revealed SYNTAX score (OR = 5.95, p Â 0.001) was an independent predictor of in-hospital outcome in patients under going primary PCI. Performance test of SYNTEX score in the setting of Primary PCI outcome showed positive predictive value 83%. Conclusions: SYNTAX score was an independent variable that can predict in-hospital outcomes of patients with acute STEMI undergoing primary PCI. Bangladesh Heart Journal 2018; 33(2) : 121-125